PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN MANAGERIAL ABILITY SEBAGAI VARIABEL MODERASI - Nusantari, Dewa Ayu Mas Putriari; Ratna Sari, Maria Mediatrix; Yadnyana, I Ketut; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022, 2022)
This research was conducted on manufacturing companies listed on the IDX from 2015 to 2019 using secondary data namely the published financial statements of manufacturing companie. The method of determining the sample using purposive sampling technique, namely the type of sample selection with certain criteria, with the number of companies used as many as 168 companies. The data analysis technique used is panel data regression analysis. The implications of this research include two things which is theoretical implications and practical implications. Theoretical implications related to the contribution of this study to agency theory in which related to firm value, tax avoidance and managerial ability. The practical implications relate to the contribution of research to capital market participant regarding the factors that affect firm value which is tax avoidance and linking these variables to managerial ability in which explains management activities through the characteristic of managers. The results of the analysis show that tax avoidance has a negative effect on firm value, and managerial ability weakens the negative effect of tax avoidance on firm value of manufacturing companies listed on BEI